PEMBANGUNAN APLIKASI E-COMMERCE PADA CV EGA INTERIOR (Information Technology and Telematics, 2013)
Abstrak   CV.Ega Interior is a company that sells interior items such as curtains, vertical blinds, bed linen, and so forth. CV. Ega interior will develop the business process by using e-commerce applications. E-commerce  applications on  CV.Ega interior was built with  the aim to provide  information  about the product  and  the type of goods sold can help expand the company's marketing and help prospective  buyers to purchase products online that can be accessed for 24 hours . With the awakening of the website is expected to help management CV. Ega Interior in expanding the marketing reach interior goods that can be accessed anywhere and anytime by consumers who will buy the goods in the online media. Keywords: E-commerce applications, interior,  online,  website.